Carbazole-dendronized thermally activated delayed fluorescent molecules with small singlet-triplet gaps for solution-processed organic light-emitting diodes. (June 2018) - Huang, Manli; Li, Yifan; Wu, Kailong; Luo, Jiajia; Xie, Guohua; Li, Lu; Yang, Chuluo
Abstract: Based on a multi-carbazole encapsulation strategy, two novel solution-processable thermally activated delayed fluorescence (TADF) molecules, named 2, 8-bis(2, 7-bis(3, 6-di- tert -butyl-9 H -carbazol-9-yl)-9, 9-dimethylacridin-10(9 H )-yl)dibenzo[b, d]thiophene 5, 5-dioxide (1CzAcDBTO ) and 2, 8-bis(9, 9-dimethyl-2, 7-bis(3, 3″, 6, 6″-tetra- tert -butyl-9′ H -[9, 3':6′, 9″-tercarbazol]-9′-yl)acridin-10(9 H )-yl)dibenzo[b, d]thiophene 5, 5-dioxide (2CzAcDBTO ), were synthesized. Both compounds exhibit excellent thermal stability and a small energy gap between the lowest singlet and triplet state, i.e., 0.02 eV for1CzAcDBTO and 0.04 eV for2CzAcDBTO, respectively. Attributed to the more effective reverse intersystem crossing process, the molecule2CzAcDBTO as the neat emitter realized better electroluminescent performances. The simplified devices with the neat dendrimers as the emissive layers exhibit significant improvements of the external quantum efficiencies (EQEs) by factors of 19.5 and 22.5, respectively compared with the device incorporating the small molecular core AcDBTO. By blending an additional TADF sensitizer with the dendrimers in a common host, enormous enhancements of efficiency and luminance were realized, e.g., a maximum EQE of 7.9% and a maximum luminance of 16380 cd/m 2 . Remarkably, the EQE remains as high as 7.4% at the high luminance of 1000 cd/m 2, revealing a negligible efficiency roll-off. Graphical abstract: Based on a multi-carbazole encapsulation strategy, two novel solution-processable TADF molecules were synthesized. With the increasing solubility, the devices performances were dramatically enhanced. Highlights: Both compounds exhibit excellent thermal stability and a small ΔΕST . The neat dendrimers based devices exhibit significant improvements compared the reference device. A maximum EQE of 7.9% and negligible efficiency roll-off are achieved by sensitizing the dendrimer.